Pengaruh Pembiayaan Bagi Hasil dan Dana Pihak Ketiga Terhadap Profitabilitas Bank Umum Syariah Dengan Non Performing Financing Sebagai Variabel Intervrening: Studi Kasus pada Bank Umum Syariah Tahun 2017-2021 - Aini Rahma; Irsad Lubis (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the effect of profit sharing financing, namely mudharabah and musyarakah and third party funds, on the profitability of Sharia Commercial Banks with the intervening variable, namely Non Performing Financing (NPF) (Z) for the 2017-2021 period. The independent variables used in this research are Mudharabah Financing (X1), Musyarakah Financing (X2), and Third Party Funds (DPK) (X3). Meanwhile the dependent variable is Profitability (Return On Assets) (Y). The research data used is secondary data, namely the amount of mudharabah financing, musyarakah financing and third party funds as well as the level of profitability (ROA) and can be obtained from the official website of the Financial Services Authority (OJK) and the Banking Annual Report. This research data consists of 35 data, where the data used is annual data. The research method used in this research is quantitative with a descriptive approach.